ANALISIS TINGKAT KEPUASAN JAMA’AH HAJI DAN UMROH TERHADAP PELAYANAN PRIMA (PT. AFI TOUR JAKARTA) - Supriadi, Yoga; Nawawi, Kholil; Arif, Suyud (EDUTECH CONSULTANT, 2019)
The reaset goal is to analyze the level of satisfaction of Umrah pilgrims. This study uses a quantitative approach. This study was conducted during the months of August-October 2019 at PT. AFI Tour. The data collection method to spread out questionnaires to 70 respondents out of a total population of 240 pilgrims. Processing data using SPSS 25.0 software support for Windows. The results of the analysis of satisfaction index worshipers at a variable intangibles with an average index of 4.59%, which shows the level of satisfaction of the congregation of 66.43% has the category of very satisfied, the variable reliability with an average index of 4.34%, which shows the level of satisfaction of the congregation of 65.73% has the category of very satisfied , the variable responsiveness with an average index of 4:09%, which shows the level of satisfaction of the congregation of 57.28% has the category of very satisfied, the guarantee variable with an average index of 4:25%, which shows the level of satisfaction of the congregation of 63.68% has the category of very satisfied, the variable empathy with an average index of 4.66%, which indicates the level of 67.96% satisfaction pilgrims have very satisfied category.